Graphene Based Terahertz Antenna Design for Modern Applications (International Journal of Innovative Research in Engineering & Management, 2021)
In the Modern communication field, transmitting data through  compact antennas like Microstrip patch antennas plays a major  role. For Mobile radiolocation, satellite services, medical  applications at Terahertz frequency range. Designing antennas for  such applications at this frequency must have less weight and good  characteristics. For this, graphene is the best suitable material for  design due to its electrical, optical, and thermal conductivity  properties. So, The Graphene-Based drilled substrate patch antenna  500 X 500 X 40 µm presents the simulation in the terahertz  frequency. The prosed antenna structure is well suitable in the ISM  (Industrial Scientific and Medical) band 1.36 THz-1.64THz 2.4 ~  2.5 GHz. Its gives a high gain -20dB. Their Properties have been  analyzed with CST for full-wave Simulations.
Keywords: Nano di-patch antenna; Graphene; THz Antenna; Modern Applications